2013
DOI: 10.1186/1471-2415-13-31
|View full text |Cite
|
Sign up to set email alerts
|

Dolosigranulum pigrum keratitis: a three-case series

Abstract: BackgroundDolosigranulum pigrum is a commensal inhabitant of the upper respiratory tract suspected to be responsible for ocular infections but no well-described case of D. pigrum corneal infection has been reported. Herein culture and PCR-sequencing-based investigations of corneal scraping specimens confirmed D. pigrum keratitis in three patients.Case presentationThree elderly patients presented with unilateral keratitis. None was a corneal-contact lens wearer, one had previous cataract surgery and another suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Our specimen was sensitive to beta-lactams, cephalosporin, fluoroquinolones, and vancomycin. However, it was intermediately resistant to erythromycin, which largely matched the CDC data [4,[6][7][8][9]. The CDC data showed that 52% of their isolates were resistant to erythromycin, with most of those resistant samples appearing in corneal collections [6].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Our specimen was sensitive to beta-lactams, cephalosporin, fluoroquinolones, and vancomycin. However, it was intermediately resistant to erythromycin, which largely matched the CDC data [4,[6][7][8][9]. The CDC data showed that 52% of their isolates were resistant to erythromycin, with most of those resistant samples appearing in corneal collections [6].…”
Section: Discussionsupporting
confidence: 73%
“…In comparison to prior reports, our patient followed patterns that predicted a favorable outcome [2][3][4][5][6][7][8][9][11][12][13][14][15]. He was a 61-year-old male with no chronic immunosuppressive conditions or medications apart from the end-stage renal disease on dialysis due to type II diabetes.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The organism has emerged as a potential pathogen in humans and has been identified in a broad spectrum of diseases, including nosocomial pneumonia and 9 and cystic fibrosis pneumonia. 10 Ocular involvement of D. pigrum has been reported in cases of a neurotrophic cornea, 11 blepharitis, 12 keratitis, 13 and bacterial conjunctivitis.…”
Section: Proposed Pathogenesis Of Phlyctenulosismentioning
confidence: 99%